Special features of using physical exercises in preparing individual programs - Danyluk, Valery; Rozputniy, Alexander; Nazarova, Inna (My University, 2013)
Traditional physical training programs focused on middle-norms and include neither individual nor typological variability and dynamics of psychological, physiological, somatic indices, making them insufficiently objective. Modern programs in physical training declare individual approach taking into account, in particular, the level of physical fitness. However, despite the practical importance, science-based procedures for individual-typological approach has not worked yet. Therefore, the current method of differential physical training is largely empirical. Hereby, physical training is an important part of the educational program of students, whose mission is to optimize learning for all students, without separating them into "capable" and "incapable" of various physical skills, develop students’ motor skills, promote social and emotional development, and cognitive component in the study of human movement.
Keywords: фізична підготовка; физическая подготовка; physical training; кафедра фізичного виховання